Thermoregulatory evaluation of triathlon suits in regards to their physiological comfort properties - Troynikov, O.; Ashyeri, E. (Procedia Engineering, 2011)
In this study 3 commercially available triathlon suits, one baseline level and 2 specialised suits, and their comprising materials are evaluated in terms of thermoregulatory performance, namely Dry Thermal Resistance, Evaporative Resistance and Permeability Index. Objective evaluation of thermal characteristic of these suits and materials is carried out by means of a Thermal Manikin where the data acquired in static, non-perspiring and perspiring conditions. Varied skin surface and sweating rates are allocated to different body zones relative to the triathlon activity, performance of the suits is evaluated, and the factors affecting their thermoregulatory characteristics are identified. The study demonstrated that the physiological comfort properties of triathlon suits are determined by both the fabrics and materials used and also the design and construction of the garments. It is possible by altering the design of the garment and, most importantly, by selection of the materials with relevant performance attributes, to engineer the garments with optimal performance.